Self-Massage Training in Overcoming Post-Training Fatigue for Running Athletes - Haryanto, Arief Ibnu; Suardika, I Kadek; Kadir, Suprianto; Nopiyanto, Yahya Eko; Garcia-Carrillo, Exal (Jurnal Pengabdian UNDIKMA, 2024)
This service aims to provide training to athletes and track coaches in Gorontalo City regarding self-massage techniques to effectively overcome post-workout fatigue so that they can improve performance and speed up muscle recovery. This service was carried out at the Nani Wartabone Sports Center, Gorontalo City, which used some equipment, namely massage beds, mattresses, foam rollers, massage guns, mats, magnetic therapy back massagers, olive oil, and face towels. The method for this service was designed through field observation procedures, coordination with administrators, Focus Group Discussions, training, and evaluation. The results of this service show that the self-massage training carried out in Gorontalo City was proven to be effective in improving the skills and knowledge of athletes and coaches in dealing with post-training fatigue. The results of the training showed very satisfying participation, productive collaboration, and good application of the material by the participants. The self-massage technique taught was successfully implemented effectively, providing a positive impact on reducing fatigue and increasing the participants' body fitness.